Factors that shape the integration of HIV and TB services in Zomba District, Malawi - Alex F. Maseko; Adam Silumbwe; Patricia Maritim; Margarate N. Munakampe; Griphin Baxter Chirambo; Choolwe Jacobs; Joseph M. Zulu (BMC Health Services Research)
Abstract Background The co-occurrence of HIV and tuberculosis (TB) presents significant challenges for effective healthcare delivery and patient outcomes. Integrating HIV and TB services has been recognised as a key strategy to optimise care and improve health outcomes. However, the factors that shape the optimal integration of these services remain unclear in many settings. This study aimed to explore the factors that influence the integration of HIV and TB services. Methods A purposive sampling technique was used to select study participants from 3 selected health facilities in Zomba, Malawi. This study used an exploratory qualitative case study and was performed from February to March 2024. A total (n = 31) of semistructured interviews were conducted. Healthcare providers (n = 12), program coordinators (n = 4), and recipients of care (n = 15) involved in the delivery of HIV and TB services were purposefully included. Thematic analysis using the Atun framework, which groups factors shaping integration around the problem, intervention, adoption system, health system characteristics and broad context, was employed. Results Increased workload among health workers and side effects among patients were reported barriers given the nature of the problem. The benefits of integrating HIV/TB services and compatibility with one’s job shaped HIV/TB integration. The adoption system-related factors included the role of volunteers and nongovernmental organisations. Health system characteristics facilitating HIV/TB integration included strong positive relationships among stakeholders, the provision of incentives and the availability of demand-generating activities. Structural challenges, a lack of financial support and shortages of commodities and supplies were health system-related barriers. Broad contextual factors facilitating HIV/TB integration included strong political will, whereas barriers included the impact of religious, sociocultural and economic factors, including the impact of natural disasters and the COVID-19 pandemic. Conclusion The effective integration of HIV and TB services is contingent upon addressing systemic and contextual barriers while leveraging facilitating factors. Enhancing health worker capacity, ensuring consistent supply chains, and fostering strong stakeholder relationships are vital steps. Additionally, comprehensive strategies that address these multifaceted issues are key to achieving successful integration and better health outcomes.